Serial evaluations at an indium‐tin oxide production facility1. Issue 3 (25th October 2012) - Cummings, Kristin J.; Suarthana, Eva; Edwards, Nicole; Liang, Xiaoming; Stanton, Marcia L.; Day, Gregory A.; Saito, Rena; Kreiss, Kathleen
Abstract Background We evaluated the effectiveness of workplace changes to prevent indium lung disease, using 2002–2010 surveillance data collected by an indium‐tin oxide production facility. Methods We assessed pulmonary function using lower limits of normal. Blood indium concentration and personal air sampling data were used to estimate exposure. Results Abnormalities were uncommon at hire. After hire, prevalence of spirometric restriction was 31% (n = 14/45), about fourfold higher than expected. Excessive decline in FEV1 was elevated at 29% (n = 12/41). Half (n = 21/42) had blood indium ≥5 µg/l. More recent hires had fewer abnormalities. There was a suggestion that abnormalities were more common among workers with blood indium ≥5 µg/l, but otherwise an exposure‐response relationship was not evident. Peak dust concentrations were obscured by time averaging. Conclusions Evolving lung function abnormalities consistent with subclinical indium lung disease appeared common and merit systematic investigation. Traditional measures of exposure and response were not illustrative, suggesting fresh approaches will be needed. Workplace changes seemed to have had a positive though incomplete impact; novel preventive interventions are warranted. Am. J. Ind. Med. 56:300–307, 2013. © 2012 Wiley Periodicals, Inc.